Influence of yearlong training on the state of cardiovascular, autonomic nervous system and physical performance in female 400 meters runners - Ye. L. Mikhalyuk; M. V. Didenko; S. N. Malakhova (Zaporozhye State Medical University, 2016)
Aim of the research - identification and comparison of heart rate variability, central hemodynamics and physical performance in 400 meters runners from the III category to masters of sports of international class (MSIC) in the annual cycle of the training process. Materials and methods. The study included 22 female athletes, 400 meters runners between the ages of 14 and 27 years (mean age - 16.8 ± 0.67 years), running experience - from 2 to 13 years (average - 4.4 ± 0.68 years) in the preparatory and competitive periods. Body length and weight of athletes were 167.9 ± 0.91 cm and 52.5 ± 0.98 kg, respectively. For the analysis of the autonomic regulation of cardiac activity mathematical methods of HRV analysis were used. Analysis and evaluation of periodic components of heart rate were carried out by means of the research of spectral parameters of autocorrelation functions. Determination of physical performance was carried out under the practical standard on the cycle ergometer. It was established that in high class sportswomen (n=12) and ones with qualifications of the II-III category (n=10) in the competitive period there were strengthening of parasympathetic effects of ANS, transformation of eukinetic circulation type (CT) into hypokinetic CT and absence of sportswomen with hyperkinetic CT. In high class sportswomen there were significant increase of the relative value of physical working capacity (PWC170/kg) by 12.33% and tendency to increase of index of functional state (IFS) by 9.46%, in sportswomen with qualifications of II-III category PWC170/kg significantly increased by 19.26%, and IFS by 17.87%. Correlation analysis conducted in both periods in the group and separately in high class sportswomen and ones with qualifications of II-III category found the relationship indicating that the increase of PWC170/kg and IFS is associated with the prevalence of hypokinetic CT and parasympathetic ANS influences. In the competitive period there were favorable changes in the functional state and the technical results of sportswomen, allowing some runners to improve their athletic qualification.